Identification of reserves of improving the quality of body castings based on the computer-integrated simulation of equipment - Насырова, Вероника Альбертовна (Technology audit and production reserves, 2013)
The paper reflects the results of studying the possibilities of identifying the reserves of improving the quality of shaped castings on the basis of the computer simulation of the processes of mold casting. Software products Solid Works and LVMFlow were used for the simulation. The purpose of such simulation is the forecasting and definition of probable formation of defects in the casting body, without conducting practical experiments that significantly reduces the expenditure of materials and time for obtaining the results. The selection of alternative ways of eliminating the porosity, associated either with the addition of feeders on the casting sides, or with the increase of the volume of feeders, based on the presented simulation results, should be made in favor of the second, since the addition of two additional feeders did not improve the result.